Fluorescent Properties of a Hybrid Cadmium Sulfide-Dendrimer Nanocomposite and its Quenching with Nitromethane - campos, bb (2010)
A fluorescent hybrid cadmium sulphide quantum dots (QDs) dendrimer nanocomposite (DAB-CdS) synthesised in water and stable in aqueous solution is described. The dendrimer, DAB-G5 dendrimer (polypropylenimine tetrahexacontaamine) generation 5, a diaminobutene core with 64 amine terminal primary groups. The maximum of the excitation and emission spectra, Stokes' shift and the emission full width of half maximum of this nanocomposite are, respectively: 351, 535, 204 and 212 nm. The fluorescence time decay was complex and a four component decay time model originated a good fit (chi = 1.20) with the following lifetimes: tau (1) = 657 ps; tau (2) = 10.0 ns; tau (3) = 59.42 ns; and tau (4) = 265 ns. The fluorescence intensity of the nanocomposite is markedly quenched by the presence of nitromethane with a dynamic Stern-Volmer constant of 25 M(-1). The quenching profiles show that about 81% of the CdS QDs are located in the external layer of the dendrimer accessible to the quencher. PARAFAC analysis of the excitation emission matrices (EEM) acquired as function of the nitromethane concentration showed a trilinear data structure with only one linearly independent component describing the quenching which allows robust estimation of the excitation and emission spectra and of the quenching profiles. This water soluble and fluorescent nanocomposite shows a set of favourable properties to its use in sensor applications.